Sudan's rheumatic fever and rheumatic heart disease guidelines: a simplified approach in an endemic country - Ali Sulafa, Khalid M.; Karrar, Zein A.; Elkurdufani, Nawal; Ibrahim, Nazik (Frontiers in Cardiovascular Medicine, 2024)
Methods: Sudan Federal Ministry of Health (FMOH) in collaboration with World Health Organization (WHO), East Mediterranean Regional Office (EMRO) assembled a committee for RHD guidelines' update. We conducted a systematic literature search from 2000-2022 in National Institute of Health Database (PubMed) under the titles: Streptococcal pharyngitis, acute rheumatic fever, rheumatic heart disease, benzathine penicillin. Best available, evidencebased practices for diagnosis and management of ARF/RHD were selected and adapted to Sudan's situation. The guidelines were critically appraised by the committee then endorsed to the MOH and WHO/ EMR noncommunicable disease departments in January 2023. This paper describes the updated guidelines Results: Simplified algorithm are provided for diagnosis of bacterial pharyngitis including 2 clinical criteria: sore throat and the absence of viral symptoms in the target age group . A simplified algorithm for diagnosis and management of ARF is adopted using 2 levels of diagnosis: suspected case at primary level where penicillin prophylaxis is started and secondary/tertiary care where echocardiography is performed and diagnosis confirmed or excluded. Echocardiography screening is recognized as the standard method for early diagnosis of RHD, however, due to the anticipated limitations, its implementation was not adopted at this time. Streptococcal skin infection is included as a precursor of ARF and a detailed protocol for benzathine penicillin administration is described.The Sudan guidelines for ARF/RHD management were updated. Endorsement of these guidelines to FMOH and WHO EMRO is expected to improve control of RHD in the region.